Notes on Assessment of Cultural Significance of the 18th-Century Old Mosque: A Case Study of the Al-Anwar Angke Mosque Jakarta - Atie Ernawati Aziz; Widjaja Martokusumo; Indah Widyastuti; Arif Sarwo Wibowo (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
This paper discusses the assessment process of the cultural significance of the Al-Anwar Angke Mosque in Jakarta. The mosque has been designated as an important cultural heritage, in which architectural, historical, and sociocultural values are explicitly demonstrated. Furthermore, the mosque was also considered a symbol of the diverse community in Batavia. However, the 18th-century mosque has undergone physical (including its details and ornaments) and environmental changes due to sociocultural, economic, and political dynamics. Therefore, continuous monitoring is essential to protect historic buildings, and cultural heritage values should be assessed periodically. The assessment of cultural significance includes aesthetic, historical, scientific, sociocultural, and spiritual criteria. Data collection and analysis are based on observation, interviews, and related literature. Furthermore, some critical notes indicate that assessment must be performed regularly and continuously. Thus, such an assessment is required to understand its values and unique artefacts. However, rather than determine the role of the Angke Mosque within its ever-changing context. As pointed out in the cultural significance assessment process, the article reveals the importance of recording and digitizing knowledge to comprehend the past, present, and future. Moreover, the appreciation might be understood differently due to the current urban dynamic. The assessment of the cultural significance of the Angke Mosque needs to accommodate community participation and a multidisciplinary approach to understanding architectural heritage, driven by the paradigm shift from a physical-based to a value-based system.